The Role of Financial Performance Mediates The Influence of Green Investment Impact on Firm Value: Environmental Regulation as a Moderating Factor - I Ketut Puja Wirya Sanjaya; Ni Luh Putu Ratna Wahyu Lestari (Jurnal Ekonomi dan Bisnis Jagaditha, 2025)
The market's reaction, which is represented in share prices, indicates the growth in the company's worth. The greater a company's share price, the greater its worth. On the other hand, environmental issues might result in a drop in a company's worth. Similar to PT. Lapindo Brantas Inc., whose careless drilling for natural gas and oil in Sidoarjo had detrimental effects on the environment and society, as well as a decrease in the value of PT's shares. Up until 2018, the largest stakeholder of PT. Lapindo Brantas Inc. was Energi Mega Persada, Tbk. This event serves as more evidence for the theory that unethical business practices can negatively affect a company's overall worth. Data from mining companies registered on the Indonesia Stock Exchange between 2018 and 2022 were used in this study. The sample strategy employed in this study was purposeful sampling. According to these standards, a total of 70 observations were made. The study's conclusions show that a company's worth can be positively impacted by both financial performance and green investments, and that this relationship can be mediated. Green investments will improve financial performance and increase the value of the organization. Environmental regulations also have a moderating effect of green innovation on financial performance